Plain language summary of publication of the 48-week results from the PHOTON study: intravitreal aflibercept 8 mg for diabetic macular edema - David M. Brown; David S. Boyer; Diana V. Do; Charles C. Wykoff; Taiji Sakamoto; Peter Win; Sunir Joshi; Hani Salehi-Had; András Seres; Alyson J. Berliner; Sergio Leal; Robert Vitti; et al. (Therapeutic Advances in Ophthalmology, 2025)
Summary What is this summary about? This is a summary of a publication about the PHOTON study, which was published in The Lancet . Diabetic macular edema (DME) is a serious and common complication of diabetes, with an estimated global prevalence of 5.5% in people with diabetes. In DME, leaky blood vessels lead to the swelling (or edema ) of the macula (the area of the retina at the back of the eye that is responsible for sharp vision), which can then lead to blurred vision and vision loss. Over-production of a protein called vascular endothelial growth factor (VEGF) is a main cause of these leaky blood vessels. To directly address the underlying problem, anti-vascular endothelial growth factor (anti-VEGF) medicine, given as an injection into the eye, can block the VEGF causing the leaky blood vessels and edema . ○ However, frequent eye injections are often required to maintain good vision and many people find it difficult to keep up with the visits and injections. Aflibercept is an anti-VEGF medicine that is approved for the treatment of DME. ○ It is recommended that people with DME receive injections of aflibercept 2 mg every 4–8 weeks after 5 initial monthly injections. The PHOTON study was carried out to determine if a higher, 8-mg dose of aflibercept , given every 12 or 16 weeks after 3 initial monthly injections, could provide the same treatment benefits as aflibercept 2 mg, given every 8 weeks after 5 initial monthly injections. What were the results? During the first year (or at 48 weeks) of the study, participants who received aflibercept 8 mg every 12 or 16 weeks following 3 initial monthly injections had similar improvements in vision when compared to those treated with aflibercept 2 mg every 8 weeks following 5 initial monthly injections with fewer injections. ○ Most participants who received aflibercept 8 mg and completed the study through 48 weeks kept their 12- or 16-week injection schedules without needing to have more frequent injections. ○ Disease severity, measured by the Diabetic Retinopathy Severity Scale score, improved by at least 2 levels at week 48 in 27% of participants who received aflibercept 2 mg every 8 weeks, 29% of participants who received aflibercept 8 mg every 12 weeks, and 20% of participants who received aflibercept 8 mg every 16 weeks. ○ Participants who received aflibercept 8 mg had similar decreases in swelling of the macula as measured by central retinal thickness compared to those treated with aflibercept 2 mg at week 48, even though fewer injections were received with aflibercept 8 mg. Adverse events in participants treated with aflibercept 8 mg were also similar to those treated with aflibercept 2 mg. What do the results mean? Often, patients with DME may find it difficult to keep up with the routine medical appointments that are required to maintain their vision. Findings showed that aflibercept 8 mg provided a similar level of improvement in vision to aflibercept 2 mg in people with DME but with fewer injections after 1 year of treatment. Treatment with aflibercept 8 mg may help to improve vision in these patients with fewer injections.